Environmental Rechtvacuum In Asean: The South China Sea Arbitration’s Environmental Precedents And Regional Implementation Challenges - Silvia Tanaman, Gunawan Widjaja, dan Songga Aurora Abadi (Jurnal Identitas, 2025)
This research aims to analyze environmental law implementation gaps (rechtvacuum) in ASEAN by focusing on the South China Sea Arbitration Award (Philippines v. China) and its impact on regional marine environmental protection. The methodology employs comparative legal analysis of 250 environmental governance documents from ASEAN published between 2016-2025, including content analysis of the arbitration award and regional implementation data. Results demonstrate that the Arbitral Tribunal established six key legal precedents: (1) environmental obligations existing independently of sovereignty disputes, (2) customary international law duties to prevent transboundary harm, (3) due diligence standards for marine protection, (4) ecosystem damage assessment frameworks, (5) mandatory EIA requirements, and (6) state responsibility for private actor environmental crimes. However, analysis of ASEAN documents reveals extremely low incorporation rates, ranging from 5% (non-existent) to 35% (moderate) across all precedent categories. Recent 2025 data shows destruction of 28.3 square kilometers of coral reef with China responsible for 65% of damage. This research reveals a sophisticated form of environmental rechtvacuum where binding legal precedents exist but regional implementation is systematically avoided through consensual paralysis, economic subordination, sovereignty fetishization, and temporal deflection.